Strain-engineered piezotronic effects in flexible monolayer MoS2 continuous thin films. (1st December 2022) - Puneetha, Peddathimula; Mallem, Siva Pratap Reddy; Im, Ki-Sik; An, Sung-Jin; Lee, Dong-Yeon; Park, Herie; Park, Kwi-Il; Shim, Jaesool
Abstract: The rapid development of flexible devices has progressed their applications in robotics, artificial intelligence, and healthcare. Herein, we used graphene and two-dimensional (2D) transition-metal dichalcogenide (TMD)-based monolayer MoS2 continuous films fabricated by chemical vapor deposition (CVD) and transferred onto a flexible polyethylene terephthalate (PET) substrate for the fabrication of a flexible device. Owing to the application of strain-engineering concepts, such as compression and stretching, the flexible device can be electromechanically operated by the piezotronic effect based on the coupling and screening phenomena. The flexible device showed significant mechanical strength with a strain-gauge value of 495 at an applied strain of − 0.34 % (i.e., compressive direction), which is ∼8.95 times higher than that of a standard metallic gauge-factor value. Furthermore, the flexible device operated at a cryogenic temperature (210 K) showed a maximum gauge-factor value at a stretching of 0.34 %, which may be due to the reduced screening effect caused by enriching the piezocharges in MoS2 . These findings pave the way for practical applications of the next generation flexible devices in several fields, including biomedical diagnoses, surgical robots, prostheses, and human-machine interfaces. Graphical Abstract: In the application of strain-engineered concepts such as compressive and stretches, the MoS2 /graphene/PET flexible device can be electromechanically operated by the piezotronic effect based on the coupling and screening phenomena. The device has significant mechanical strength with a strain-gauge value of 495 at an applied strain of − 0.34%, which is nearly 8.95 times larger than that of a metallic gauge value. ga1 Highlights: CVD-grown monolayer MoS2 continuous thin films were used. Tune/control of electromechanical properties based on the piezotronic effect in the compressive/stretching modes. The flexible device shows 8.95 times larger than that of a standard strain-gauge value. Reduced screening effect by enriching piezocharges in the MoS2. This piezotronic device pave the way for future practical device applications.